Analysis of the Effect of Fixators and pH Conditions on the Color Absorption of Cotton with Natural Teak Leaf Dyes (Tectona grandis Linn. f.) - Sigit Priatmoko; Nova Eka Rahmawati; Harjono Harjono; Triastuti Sulistyaningsih; Nala Izzul Muna (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Growing concern about the environmental impacts of synthetic dyes has renewed interest in plant-based colorants for sustainable textile dyeing. Teak leaves (Tectona grandis Linn. f.) are rich in polyphenolic compounds with strong chromophoric properties, but the influence of fixation conditions and dye-bath pH on fabric performance requires further clarification. This study evaluated the effects of mordant type and dye-bath pH on color intensity and washing fastness of cotton fabrics dyed with teak leaf extract. Cotton samples were dyed at pH 4, 6, 8, 10, and 12, then post-mordanted using alum, ferrous sulfate, or tamarind extract. Color characteristics were quantified using the CIE Lab* system, and washing fastness was assessed following SNI ISO 105-C06:2010. Ferrous sulfate consistently produced the darkest shades and the highest washing fastness ratings (TLW 3–4 to 4), likely due to stable metal ligand complex formation among Fe²⁺ ions, dye molecules, and cellulose fibers. Mildly alkaline dye baths (pH 8–10) enhanced color depth, whereas extreme alkalinity (pH 12) decreased dye uptake, presumably because stronger electrostatic repulsion limited adsorption. Overall, teak leaf extract shows strong potential as an eco-friendly natural dye, and the results emphasize that careful mordant selection and pH optimization are essential to achieve durable coloration for sustainable textile processing.